Kriteria Cauchy Integral Riemann di Ruang Riesz - Muhammad Arifin Ilham; Jerrico Nugroho; Made Tantrawan (Limits: Journal of Mathematics and Its Applications, 2024)
In 2008, Boccuto and Candeloro [4] introduced a variant of Riemann integral for Riesz valued functions defined on an order interval in a Riesz space. In this paper, we present an equivalent definition and several Cauchy criterion versions of the integral. Furthermore, some applications of the Cauchy criterion are provided.